Validación de la metodología Corine Land Cover (CLC) para determinación espacio-temporal de coberturas: caso microcuenca de la quebrada Mecha (Cómbita, Boyacá), Colombia (2016)
The Corine Land Cover methodology, is a french methodology adapted by the Agustin Codazzi Geography Institute (Igac) and the Hidrology, Meteorology and Enviromental Studies (Ideam) for Colombia and it is the assessment of land cover using Landsat satelilite images. In this research, the space-temporary assessment of the watershed coverage of the Mecha creek in the Chicamocha river basin was done using Landsat 8 images, between 2014 and 2015, wich were orthorectified, combined using Erdas Software. These were also cut according to the spectral signatures of the selected bands in the ArcGis 10.0 program, and adjusted with images of Google Earth Pro and configured with the use of the National legend coverages at 1:100.000 proposed by Ideam. It was also observed that the moor vegetation is highly fragmented, with a tendency to completely disappear, because of increasing agricultural areasand mining operations; significantly deteriorating the wáter capacity of the creek that supplies the aqueduct of the Municipality of Oicatá. It is concluded that this methodology becomes a hifhly reliable tool for determining spatio-temporal coverage changes in order to be the basis for the decisión-making related coverage in order to protection and conservation.